Corporate social responsibility and financial performance in the banking industry: a comparative study of Australia and Vietnam - Nguyen, Ha Van; Vu, Diem-Phuc Thi; Pham, Giang Huong; Phan, Huong-Giang Thi; Le, Khanh Gia (Journal of International Economics and Management, 2023)
While investigating the financial implications of corporate social responsibility (CSR) is important for all kinds of enterprises, such an examination is crucial for firms operating in the banking industry given their essential role in boosting economic development in any nation. Therefore, this study aims to examine the relationship between CSR and financial performance in a sample of banks in Australia and Vietnam. Content analysis was employed to evaluate CSR information and multivariate regressions were used to assess the financial effects of CSR practices. The research findings show a significantly positive association between CSR and financial performance. Moreover, this positive relationship is more pronounced among Vietnamese banks than among their Australian counterparts. Our empirical evidence remains unchanged in a battery of robustness tests. Consequently, these findings have practical implications for commercial bank managers, policymakers, and investors.